Implementing Comprehensive Security Through Institutional Synergy: Indonesia's Total People’s Defense Framework in ASEAN Defense Minister’s Meeting (ADMM) Cooperation - Syarifuddin, Kurniawan Firmuzi (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2025)
This study examines Indonesia’s implementation of comprehensive security through institutional synergy within the ASEAN Defense Ministers’ Meeting (ADMM) framework, grounded in the constitutional doctrine of Total People’s Defense (Sistem Pertahanan Rakyat Semesta). In the context of multipolar geopolitics and intensifying nontraditional security challenges, it explains an implementation gap in which the whole-of-government mandate embedded in Total People’s Defense is not translated into consistent domestic coordination for ADMM engagement. Existing research emphasizes Indonesia’s geopolitical strategy or ADMM’s regional architecture, leaving domestic organizational and bureaucratic impediments underexamined. A qualitative phenomenological case study combined observation of 15 ADMM activities (2020–2023), analysis of policy documents including the State Defense Policy Guidelines (2020–2024), and interviews with eight senior policymakers. Three coordination failures were identified: 75 percent of non-defense officials were unfamiliar with policy provisions assigning their agencies as primary responders to nontraditional threats; 80 percent of ADMM activities relied on ad hoc rather than routine inter-agency coordination; and follow-up mechanisms were absent for integrating multilateral commitments into domestic planning and budgeting. Consequently, BNPB, BSSN, and the Ministry of Health remained peripheral despite statutory mandates, reinforcing fragmentation that constrains Indonesia’s capacity to advance regional security governance and fulfill its ADMM leadership role. It is concluded that conceptual alignment between Total People’s Defense and ADMM comprehensive security is necessary but insufficient without institutionalized coordination. Three interventions are proposed: structured orientation and quarterly briefings, formal role delineation through regulation, and a standing ADMM Coordination Working Group to ensure continuity and domestic policy integration.